Wastewater Management and Its Role in Achieving the Various Goals of Sustainable Development: A Review - Ali, Qahtan Adnan; Ghareeb, Ozdan Akram (Emerging Issues in Environment, Geography and Earth Science Vol. 7, 2024)
In this study, the role of water sector management represented by wastewater in achieving the goals of sustainable development was clarified. Wastewater management to prevent the problems resulting from it requires adopting cost-effective and applicable methods in line with the goals of sustainable development. Today, the world aspires to reach sustainable development goals (SDGs) endorsed by the United Nations, and assessing the fundamental interest of modernistic technology in achieving the SDGs is very important for planners as well as stakeholders. Sustainable development has the characteristic of being devoid of negative impact on society and the environment, so its goals can be defined as a road map to achieve more sustainability and a better future for all individuals in this world. An in-depth analysis of the goals and their interactions with each other reveals that wastewater treatment participate in implementing eleven of the seventeen sustainable development goals due to its capability to raise the amount of water available. Among the most relevant SDGs are: eliminating hunger by providing the patency of water that can be used for agriculture, being healthy by beneficent water quality and availability of clean water, clean energy, improving water recycling, biogas production, living underwater by reducing wastewater discharge. We discussed the difficulties associated with implementing these goals, by proposing a series of indicators to evolve the importance of wastewater treatment plants in SDGs. The current review article confirmed the considerable impact of wastewater treatment on achieving the internationally approved SDGs. Water scarcity must be dealt with comprehensively, all alternatives for water supply must be considered and the magnitude of this objective must be brought to the interest of relevant organizations.